Association between opioid use and survival in advanced non small cell lung cancer patients treated with immune checkpoint inhibitors - Luigi Liguori; Stefano Pepe; Valentina Pagliara; Rosario De Feo; Alessandro Ottaiano; Francesco Perri; Giovanna Polcaro; Valeria Conti; Cristina R. Ferrone; Francesco Sabbatino; Marco Cascella (Scientific Reports)
Abstract Cancer-related pain is a frequent challenge among non-small cell lung (NSCLC) cancer patients, particularly for those with advanced disease and/or bone metastases. Opioids are the mainstay of treatment for moderate to severe cancer-related pain. However, emerging lines of evidence suggest that concomitant opioid use may be associated with poor survival outcomes in advanced NSCLC patients treated with immune checkpoint inhibitors (ICIs). We analyzed the impact of concomitant opioid use on survival outcomes of advanced NSCLC patients treated with ICIs. Correlations between baseline clinical-pathological characteristics and survival outcomes were assessed using log-rank tests while multivariate survival analyses were performed using the Cox proportional hazards model. Among patients treated with ICI as monotherapy and those treated with ICI as second or subsequent lines of treatment, concomitant opioid use was correlated with decreased progression-free survival (PFS) (p = 0.0460 and p = 0.0490) and overall survival (OS) (p = 0.0380 and p = 0.0230) in univariate analyses. However, in multivariate analyses, concomitant opioid use was not independently correlated with survival outcomes. Instead, ECOG PS ≥ 2 and bone metastases emerged as strong predictors of decreased PFS and OS. Despite limitations, our findings highlight that concomitant opioid use does not independently correlate with poor survival outcomes in this setting of patients.